2003
DOI: 10.1007/s00464-003-9051-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in situs inversus totalis: The importance of being left-handed

Abstract: Since laparoscopic cholecystectomy has become the standard procedure for the treatment of gallstone disease, several cases have been reported in patients with situs inversus. These cases require more technically demanding procedures due to the symmetrical disposition of the anatomy. Thus, handedness could influence the performance of these operations. The two of us (L.M.O.) and (J.M.B.), a right-handed and a left-handed surgeon, respectively, placed the instruments in reverse mode from that used in orthotopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 12 publications
(14 reference statements)
1
75
0
Order By: Relevance
“…In the reports described previously, the surgeon dissected with his left hand, or asked for assistance to grasp the neck of the gall bladder while he dissected the Calot's triangle. 7,8 In our case, both surgeons were right-handed; therefore the technique had to be adjusted. It is much easier for a left-handed surgeon to perform laparoscopic cholecystectomy in such patients.…”
Section: Discussionmentioning
confidence: 89%
“…In the reports described previously, the surgeon dissected with his left hand, or asked for assistance to grasp the neck of the gall bladder while he dissected the Calot's triangle. 7,8 In our case, both surgeons were right-handed; therefore the technique had to be adjusted. It is much easier for a left-handed surgeon to perform laparoscopic cholecystectomy in such patients.…”
Section: Discussionmentioning
confidence: 89%
“…Positioning of the surgical team and port placements described in the literature are often a mirror image of the protocols used for conventional laparoscopic cholecystectomy. However, the ergonomics of a right-handed surgeon standing on the right side of the patient demand that either he crosses hands so as to allow the right hand to operate through the epigastric port 4 or use the assistant to retract the Hartmann's pouch from the left side 5 or as we have described here, use the epigastric port to retract with the left hand and operate with the right hand through the lateral subcostal port. The surgeon standing at the foot end, in between the legs of the patient while the patient is in a Lloyd-Davis position, is an alternative, as is delegating to a left-handed surgeon!…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report the advantage of a left-handed surgeon, but a right-handed specialist can also perform the procedure by changing his position [4,5,6,7]. Young Wan Kim et al reported two cases of SIT.…”
Section: Discussionmentioning
confidence: 99%